Two-dimensional analytical investigation of coupled heat and mass transfer and entropy generation in a porous, catalytic microreactor. (April 2018) - Hunt, Graeme; Karimi, Nader; Torabi, Mohsen
Highlights: Two-dimensional analytical solutions for the temperature and concentration fields. Thicknesses of the microstructure is most influential in altering the temperature fields. Nusselt number is heavily affected by the configuration of the microstructure. Thermal diffusion of mass is usually the dominant source of irreversibility. Abstract: Influences of the solid body of microreactors (or the microstructure) upon the transfer processes and hence on the performance of microreactors have been recently emphasised. Nonetheless, the subtle connections between microstructure design and micro-transport phenomena are still largely unknown. To resolve this, the current paper presents an analytical study of the advective-diffusive transport phenomena in a microreactor filled with porous media and with catalytic surfaces. The system under investigation includes the fluid and porous solid phases inside a microchannel with thick walls and subject to uneven thermal loads. The thermal diffusion of mass, viscous dissipation of the flow momentum and local thermal non-equilibrium in the porous medium are considered. The axial variations of heat and mass transfer processes are also taken into account and two-dimensional solutions of the temperature and concentration fields are provided. The local and total entropy generation within the system are further calculated. The results clearly demonstrate the major influences of thick walls on the thermal behaviour and subsequently on the mass transfer and entropy generation of the microreactor. In particular, the Nusselt number is shown to be strongly dependent upon the configuration of microstructure such that it decreases significantly by thickening the walls. The results also demonstrate that for finite Soret numbers the total irreversibility of the system is dominated by the Soret effect. The analytical results of this work can be further used for the validation of future numerical analyses of microreactors.